The Influence of Foreign Exchange Policy from Export Proceeds, Import Payments, Inflation Rate, and Rupiah Exchange Rate on Foreign Direct Investment in Indonesia - Prayoga, Dyka Setyo; Purnomo, Didit (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Various factors influence foreign direct investment in Indonesia. This study's main objective is to determine the influence of foreign exchange policies resulting from exports, imports, inflation rates, and exchange rates on foreign direct investment (FDI) in Indonesia in 2018-2022. This data was obtained from the Central Statistics Agency, Bank Indonesia, Ministry of Finance and Trade. The analysis technique used in this research is multiple linear regression. Apart from that, a t-test can be carried out to determine the significance of the influence of the independent variable on the dependent variable. The calculation results show that the Export, Import, and Inflation variables in the short term and long term have a positive and significant effect on foreign direct investment in Indonesia, while the exchange rate does not have a positive and significant effect on Foreign Direct Investment. Variables This research is quantitative research using time series financial data from 2018-2022.